1996
DOI: 10.1073/pnas.93.16.8356
|View full text |Cite
|
Sign up to set email alerts
|

The folding mechanism of larger model proteins: role of native structure.

Abstract: The folding mechanism of a 125-bead heteropolymer model for proteins is investigated with Monte Carlo simulations on a cubic lattice. Sequences that do and do not fold in a reasonable time are compared. The overall folding behavior is found to be more complex than that of models for smaller proteins. Folding begins with a rapid collapse followed by a slow search through the semi-compact globule for a sequence-dependent stable core with about 30 METHODSWe generated a data base of 200 sequences, tested each for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 37 publications
8
71
2
1
Order By: Relevance
“…Consistent with the "thousands to millions" of degenerate optimal conformations estimated from explicit enumeration, hN HP i ≈ 10 4 for L ¼ 48. At a higher level of chemical accuracy, for a L ¼ 80 lattice chain consisting of the 20 types of amino acids and with a unique native fold, it was found that at most 10 6 Monte Carlo steps were required to reach the native fold (22). This is in agreement with Eq.…”
Section: Resultssupporting
confidence: 78%
“…Consistent with the "thousands to millions" of degenerate optimal conformations estimated from explicit enumeration, hN HP i ≈ 10 4 for L ¼ 48. At a higher level of chemical accuracy, for a L ¼ 80 lattice chain consisting of the 20 types of amino acids and with a unique native fold, it was found that at most 10 6 Monte Carlo steps were required to reach the native fold (22). This is in agreement with Eq.…”
Section: Resultssupporting
confidence: 78%
“…Recent 'dead-time' labelling experiments [23] reveal the formation of an embryonic native-like structure in the h-domain at this very early stage of folding which, although only marginally stable, is probably significant in laying the foundations for the later stages of folding. Interestingly, such secondary structure with native-like character has been shown to speed up the search in the collapsed state for the nativelike folding 'core' in simulations of the folding of a 125-mer protein [24]. The hydrophobically collapsed state which is formed at the onset of the folding process of lysozyme has been suggested to have properties characteristic of equilibrium molten globule states [14,[17][18][19][20][21]23].…”
Section: The Lysozyme Story So Farmentioning
confidence: 99%
“…Indeed, sequences are usually generated and tested for its ability to fold rapidly in an small and specific range of temperature [39], even knowing that this procedure eliminates many suitable structures that would otherwise be important for kinetic studies. But a new perspective emerges when local thermal fluctuations experienced by nanoscale structures is associated with its spatial characteristics (as its size and degrees of freedom), by means of the parameter q from the nonextensive statistical mechanics.…”
Section: Final Comments and Conclusionmentioning
confidence: 99%